BAHASA VULGAR PADA NAMA MAKANAN DI MEDIA MASSA DETIKCOM DAN IMPLIKASINYA - Syamsul Anwar; Aifa Inayati; Afsun Aulia Nirmala (Sasando, 2023)
Language is a communication tool that humans use to communicate with other people. The people who use the language come from the upper, middle and lower classes. Based on the community group, the language used varies. Differences in language variations are caused by certain factors. Factors that influence variations in the language used include social factors and situational factors. Nowadays the use of vulgar language is starting to become widespread among society. The implication of vulgar language in learning Indonesian in high school is in learning to speak, especially for communication. Key words: l media, implications